Flunarizine prevents hepatitis C virus membrane fusion in a genotype‐dependent manner by targeting the potential fusion peptide within E1. Issue 1 (9th October 2015) - Perin, Paula M.; Haid, Sibylle; Brown, Richard J.P.; Doerrbecker, Juliane; Schulze, Kai; Zeilinger, Carsten; von Schaewen, Markus; Heller, Brigitte; Vercauteren, Koen; Luxenburger, Eva; Baktash, Yasmine M.; Vondran, Florian W.R.; et al.
Abstract : To explore mechanisms of hepatitis C viral (HCV) replication we screened a compound library including licensed drugs. Flunarizine, a diphenylmethylpiperazine used to treat migraine, inhibited HCV cell entry in vitro and in vivo in a genotype‐dependent fashion. Analysis of mosaic viruses between susceptible and resistant strains revealed that E1 and E2 glycoproteins confer susceptibility to flunarizine. Time of addition experiments and single particle tracking of HCV demonstrated that flunarizine specifically prevents membrane fusion. Related phenothiazines and pimozide also inhibited HCV infection and preferentially targeted HCV genotype 2 viruses. However, phenothiazines and pimozide exhibited improved genotype coverage including the difficult to treat genotype 3. Flunarizine‐resistant HCV carried mutations within the alleged fusion peptide and displayed cross‐resistance to these compounds, indicating that these drugs have a common mode of action. Conclusion : These observations reveal novel details about HCV membrane fusion; moreover, flunarizine and related compounds represent first‐in‐class HCV fusion inhibitors that merit consideration for repurposing as a cost‐effective component of HCV combination therapies. (Hepatology 2016;63:49–62)